Trauma dan Ingatan Perempuan dalam Korpus Uterus: Analisis Psikoanalisis Freud - Winda Novianti; H. Halimah; S. Sumiyadi; Rudi Adi Nugroho (Balai Bahasa Sulawesi Selatan, 2026)
This study examines the representation of women’s trauma and memory in Sasti Gotama’s novel Korpus Uterus through Sigmund Freud’s psychoanalytic perspective. The novel presents the female body, particularly the uterus, not merely as a biological entity but as a symbolic space in which pain, repression, fear, and resistance are articulated. This study employs a descriptive qualitative method with close reading as the main technique of data collection. The data consist of narrative, monologue, and dialogue units that reflect traumatic experience, the re-emergence of memory, intrapsychic conflict, and ego defense mechanisms. The analysis focuses on the dynamics of id, ego, and superego in explaining how traumatic experience is repressed, negotiated, and brought back into consciousness. The findings indicate that trauma in the novel is closely related to power relations, moral stigma, and reproductive pressure imposed on women’s bodies. Memory appears as a psychological mode through which unresolved traumatic experience returns in emotional, symbolic, and behavioral forms. Thus, Korpus Uterus portrays the uterus as a symbolic site where bodily experience, psychic conflict, and social control intersect. AbstrakPenelitian ini mengkaji representasi trauma dan ingatan perempuan dalam novel Korpus Uterus karya Sasti Gotama melalui perspektif psikoanalisis Sigmund Freud. Novel ini menghadirkan tubuh perempuan, khususnya rahim, bukan semata-mata sebagai entitas biologis, melainkan sebagai ruang simbolik tempat luka, represi, ketakutan, dan perlawanan dimaknai. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data berupa close reading. Data penelitian berupa satuan narasi, monolog, dan dialog yang memperlihatkan pengalaman traumatis, kemunculan kembali ingatan, konflik intrapsikis, serta mekanisme pertahanan ego. Analisis difokuskan pada dinamika id, ego, dan superego untuk menjelaskan bagaimana pengalaman traumatis ditekan, dinegosiasikan, dan dimunculkan kembali ke dalam kesadaran tokoh. Hasil penelitian menunjukkan bahwa trauma dalam novel ini berkaitan erat dengan relasi kuasa, stigma moral, dan tekanan reproduktif yang bekerja atas tubuh perempuan. Ingatan tampil sebagai bentuk psikologis yang menghadirkan kembali pengalaman traumatis yang belum terselesaikan melalui gejala emosional, simbolik, dan perilaku tokoh. Dengan demikian, Korpus Uterus merepresentasikan rahim sebagai ruang simbolik tempat pengalaman tubuh, konflik psikis, dan kontrol sosial saling berkelindan.